Gray matter changes in panic disorder: A voxel-based meta-analysis and meta-analytic connectivity modeling. (30th December 2018) - Wu, Yun; Zhong, Yuan; Ma, Zijuan; Lu, Xin; Zhang, Ning; Fox, Peter T.; Wang, Chun
Highlights: Patients with panic disorder have gray matter deficits in the bilateral dorsomedial prefrontal cortex (DMPFC), left dorsolateral prefrontal cortex (DLPFC), right insula, right superior temporal gyrus (STG), right middle temporal gyrus (MTG) and right superior orbital frontal cortex (OFC) consistently across all the eligible VBM studies. Right STG, left DMPFC and right OFC have a co-atrophy relationship with each other and these regions are related to the behavior domains of audition, music, emotion and execution. Left DLPFC co-activates with bilateral DMPFC and these regions are related to the behavior domains of social cognition and emotion of sadness. Abstract: Magnetic resonance imaging (MRI) studies of panic disorder (PD) have discovered various damaged brain regions, with heterogeneous results across studies. The present study used meta-analytic approaches to discover gray matter (GM) changes consistently detected in PD and to characterize the functional and connectivity profiles of these regions. In the present study we first conducted an activation likelihood estimation (ALE) meta-analysis of eight eligible whole-brain VBM studies. Then, meta-analytic connectivity modeling analyses (MACMs) were used to provide co-atrophy and co-activation profiles across all the experiments stored in BrainMap. Lastly, the co-atrophied and co-activated regions were analyzed using functional decoding to reveal their functions. Lower gray matter volume was found in the bilateral dorsomedial prefrontal cortex (DMPFC), left dorsolateral prefrontal cortex (DLPFC), right insula, right superior temporal gyrus (STG), right middle temporal gyrus (MTG) and right superior orbital frontal cortex (OFC). Significant co-atrophies were found in the STG, DMPFC and OFC and co-activations were found between the left DLPFC and bilateral DMPFC. Decreased gray matter volume in STG, OFC, DLPFC and DMPFC and their co-atrophy and co-activation patterns indicate the damaged higher cognitive functions in PD and suggest that cortical regions are important structural imaging biomarkers in PD.